Wisata Halal Di Antara Keuntungan Ekonomi Dan Politis - Laras, Ananda Putri; Gunawijaya, Jajang (Journal of Indonesian Tourism and Policy Studies, 2017)
The obedience of Moslem in keeping the commandments and away from God’s prohibitions is the cultural value that forms halal tourism market. This thesis aims to find how a conventional hotel interpret and implement halal tourism policy, as well as how the implication is. My position is in the middle of profit and loss debate of halal tourism, but I am trying to find the right strategy of implementation and non-material implication. This research problems are answered through qualitative approach and ethnography method, while the data are reduced through observation, participation of observation, formal interview and literature review. My findings show that hotel interpret halal tourism only as added value on product and service so the managers aren’t so enthusiastic about the implementation. Eventually, this cause material goal aren’t achieved. Halal tourism is not profitable and not inflict to a financial loss. On the other hand, the hotel is getting a benefit from the implementation of this policy, that is increasing motivation of kitchen staff for working because they are Moslem.